Bykov's novel 'ZhD' in the context of contemporary Russian literature development tendencies - D.V. Novokhatskiy (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper analyzes D. Bykov's novel “ZhD” ('Living Souls') in the context of various tendencies in the current literary process in Russia. The novel features secret history and conspiracy theory, with strong journalistic influences. The analysis makes use of such concepts as magical historicism, internal colonization, and localization. In order to define the regularities of Russian history and to find the ways out of the social crisis, “ZhD”, which is typical for alternate histories, models a virtual Russia placed in a conventional chronotope. Coherently with the concept of magical historicism, the philosophy of Russian history is interpreted via mythologization of the reality and employment of a fairytale. The mythology of the novel is based on the idea of “stopped” history caught in natural iterative cycles. The paper claims that magical historicism can be caused by localization processes related to national consolidation and, thus, creating the necessity to shape the image of the other, for instance, the image of the enemy. The author rejects the two-part model of the enemy based on the state ideology (internal – external enemy) and designs an original three-part model (Khazars – Varangians – Russians). According to D. Bykov, the reason of the present social crisis is not the erratic application of various models of the state, but the peculiarities of Russian mentality, and the only way to break the cycle is to change the spiritual values of the society.